DNA-based Cryptography for Internet of Things Security: Concepts, Methods, Applications, and Emerging Trends - Ţălu, Mircea (Universitas Ahmad Dahlan, 2025)
DNA-based cryptography is an emerging field that combines molecular biology and computational security to develop novel encryption, secure data storage, and steganographic techniques. It offers a promising alternative to traditional cryptographic systems, addressing challenges like storage efficiency, robustness, and resistance to computational attacks. In the era of the Internet of Things (IoT), where massive networks of interconnected devices continuously generate and exchange sensitive data, ensuring secure communication and storage has become a critical challenge. DNA-based cryptography presents a unique opportunity to enhance IoT security by offering ultra-secure encryption methods that exploit DNA’s vast information density and inherent randomness. These encryption methods leverage the complexity of DNA encoding - such as nucleotide substitution, DNA strand pairing, and biological operations like splicing and amplification - to create security layers that are difficult to decipher using conventional computational techniques. Recent advancements in DNA synthesis, sequencing, and encoding methodologies have facilitated the development of encryption schemes tailored for IoT applications, enabling lightweight, high-capacity security solutions that outperform traditional cryptographic methods. Beyond IoT, DNA-based cryptography also holds potential in areas such as secure biomedical data storage, digital rights management, and archival of sensitive governmental or historical information, demonstrating its broader applicability across diverse domains. Future research should optimize DNA encoding, improve storage technologies, and harness artificial intelligence for real-time threat detection, automated encryption, and adaptive security in IoT systems. This review analyzes DNA-based cryptographic methods, including natural and pseudo-DNA encryption, DNA-based steganography, and hybrid models, while uniquely exploring their IoT applications, emerging trends, practical implementations, key advantages, challenges, and future research directions.